Prevalence, clinical impact and costs of hyperkalaemia: Special focus on heart failure. (31st March 2021) - Maggioni, Aldo P.; Dondi, Letizia; Andreotti, Felicita; Calabria, Silvia; Iacoviello, Massimo; Gorini, Marco; Gonzini, Lucio; Piccinni, Carlo; Ronconi, Giulia; Martini, Nello
Abstract: Background: Hyperkalaemia is a potential life‐threatening electrolyte abnormality. Although renin‐angiotensin‐aldosterone system inhibitors (RAASi) are potentially life‐saving, they may contribute to hyperkalaemia. Methods: The prevalence, comorbidities, comedications and 1‐year outcomes of patients admitted or treated for hyperkalaemia were investigated in a large healthcare administrative database including 12 533 230 general population inhabitants. A similar analysis was performed in the Italian Network on Heart Failure (IN‐HF), a cardiology registry of 1726 acute and 7589 chronic HF patients, stratified by serum potassium. General practice healthcare costs related to hyperkalaemia were also assessed. Hyperkalaemia was defined by hospital coding, potassium‐binder prescription or serum levels (mild: 5‐5.4, moderate‐severe: ≥5.5 mmol/L). Results: In the general population, the prevalence of hyperkalaemia was 0.035%. After excluding patients on haemodialysis, hyperkalaemia in the community (n = 2314) was significantly and directly associated with diabetes, chronic kidney disease, HF, RAASi prescriptions, 1‐year hospitalisations and threefold annual healthcare costs, compared to age‐ and sex‐matched non‐hyperkalaemic subjects (n = 2314). In the IN‐HF registry, hyperkalaemia affected 4.3% of acute and 3.6% of chronic patients and was significantly associated with diabetes, kidney disease and lesser use of RAASi, compared to normokalaemic patients. Among patients hospitalised for acute HF, those with hyperkalaemia at entry had significantly higher 1‐year all‐cause mortality compared with normokalaemic patients, even after adjustment for available confounders. Conclusions: Hyperkalaemia in the general population, although uncommon, was associated with increased hospitalisations and tripling of healthcare costs. Among HF patients, hyperkalaemia was common and associated with underuse of RAASi; in acutely decompensated patients, it remained independently associated with 1‐year all‐cause mortality.